Quality of nurses’ working life in the perimenopausal period: influence of selected factors of work environment in medical institutions - Nowakowska, Iwona; Rasińska, Renata; Głowacka, Maria Danuta (Menopause Review/Przegląd Menopauzalny, 2012)
Introduction: An uneasy period in women’s lives, which is perimenopause, is associated with the appearance of symptoms and behavioural changes characteristic of menopause. It is also a time of professional activity. The analysis of factors in the work process may contribute to the improvement of work organisation and the increase in quality of work and professional satisfaction, despite the presence of symptoms associated with menopause. Objective: to present opinions of professionally active nurses in the perimenopausal period on the assessment of quality of working life from the point of view of selected factors of work environment and their self-efficacy. Material and methods: The study covered 169 nurses in the perimenopausal period, working in hospital wards in two provinces. In order to obtain the research material, a survey was conducted by means of a questionnaire prepared by the authors (questions concerning opinions on selected factors of work environment related to the work organisation) and the Generalized Self-Efficacy Scale (GSES). To analyse the empirical material, a statistical package IBM SPSS Statistics 19 was used. χ ² test and the Yule’s j coefficient were used, at a significance level p < 0.01. Results: There is a strong relationship between the evaluation of nurses’ work organisation and the atmosphere in the workplace (χ ² = 45.737, j = 0.520), performing tasks in teams (χ ² = 72.090, j = 0.653), number of staff on duty in relation to needs (χ ² = 59.131, j = 0.592), equipment in the workplace (χ ² = 70.973, j = 0.648) and participation in decision-making processes (χ ² = 58.209, j = 0.587), and also the opportunities for professional development and promotion (χ ² = 51.568, j = 0.552). Most women highly evaluated their self-efficacy, despite different perception of organisational factors in the hospital (χ ² = 9.492). Conclusions : Evaluation of work organisation of nurses in the perimenopausal period depends on selected determinants of the work environment. Among the respondents aged 41-55, there was no relationship between work organisation and evaluation of self-efficacy.